Graffiti: art enhancing or denigrating architectural monuments and the city? - Mejía Franciscolo, Amanda (Universidad de Lima. Carrera de Arquitectura, 2019)
Nowadays, buildings considered to be historic heritage are not under the eyes of new generations, which would result in falling them into oblivion and being several times damaged by spray-painted signatures: vandalisms since they are forbidden by the law. However, graffiti does not only imply these “careless” signatures. For example, it also includes artistic murals, a practice which communicates a message for passers-by with a more professional nature. This paper seeks to find the way in which both works of art —historic heritage and graffiti— reach a harmonious relation and complement each other. To achieve this, it is necessary the creation of a series of parameters to regulate the artistic intervention.